Management of Islamic Boarding Schools in Preparing Entrepreneurs at Sheikh Abdurrahman Shiddiq II Islamic Boarding School, Tembilahan, Riau, Indonesia - Indra Wahyuni Firli Fangestu; Siti Marpuah (Journal of Social Transformation and Regional Development, 2024)
Entrepreneurship is all activities to create something that can be added value from an economic point of view. In Indonesia, there is a relatively small number of entrepreneurs compared to other nations. For this reason, the younger generation must develop the entrepreneurial sector to contributing to the nation’s economic progress. So as students, they need to be prepared to confront the challenges of the era, by instilling entrepreneurial spirits in them so that they can become capital in adapting to the era of disruption. This research focuses on islamic boarding school management in preparing entrepreneurs, as well as the supporting and inhibiting factors at the Sheikh Abdurrahman Shiddiq II Islamic Boarding School on Pelajar Street Tembilahan Riau Indonesia. The purpose of this research is to determine islamic boarding school management practices in preparing entrepreneurs and determine the supporting and inhibiting factors. Data was gathered through observations, interviews, and documentation methods and was presented in a qualitative descriptive. Based on the research results, the following results were obtained: The management of preparing entrepreneurs at Sheikh Abdurrahman Shiddiq II Islamic Boarding School which includes planning, organizing, actuating, and controlling has been effective, but there are specific aspects requiring attention during the evaluation stage. There are four supporting factors include: 1) extensive land, 2) sufficient facilities and infrastructure, 3) enthusiasm from students, 4) and the pressence of entrepreneurial role models in the islamic boarding school. There are three inhibiting factors are: 1) budget constraints, 2) lack of transparency of the local government, 3) lack of harmony between the duties and responsibilities within the Islamic Boarding School Economic Business Division.